2019
DOI: 10.3389/fmats.2019.00252
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Co3+ Doped TiO2 by Co-precipitation Route and Its Gas Sensing Properties

Abstract: Undoped and Co-doped TiO 2 nanoparticles were synthesized by a facile co-precipitation method and calcined at 700 • C. The phase identification carried out by XRD measurements and Raman spectroscopy analysis of calcined powders reveals the formation of mainly anatase phase for undoped TiO 2 , and 0.5 mol.% Co-doped TiO 2 whereas rutile phase for 1 mol.% Co-doped TiO 2 . The sensors prepared with these powders deposited on interdigital (IDE) sensor platforms were tested toward NO 2 and H 2 sensing properties at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…Peaks at 151, 390, 510, and 627 cm −1 are ascribed to anatase phase modes E g , B 1g , A 1g , and E g , respectively. 59 The strength of the B 1g , A 1g , and E g peaks decreased after Co doping and carbothermal reduction (Fig. S1a † ).…”
Section: Resultsmentioning
confidence: 99%
“…Peaks at 151, 390, 510, and 627 cm −1 are ascribed to anatase phase modes E g , B 1g , A 1g , and E g , respectively. 59 The strength of the B 1g , A 1g , and E g peaks decreased after Co doping and carbothermal reduction (Fig. S1a † ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous results on undoped and Al, Cr and Co-doped TiO 2 , 600 °C was chosen as the optimum sensing temperature in this work [ 21 , 23 ]. In fact, both the sensor signal and response time decrease when the temperature increases.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, anatase TiO 2 seems to be the less suitable candidate for wide use as a high-temperature H 2 sensor. Previous studies have reported that this disadvantage can be overcome by suitably doping the TiO 2 [ 21 , 22 , 23 , 24 , 25 , 26 ]. Another main drawback of a resistive semiconductor metal oxide-based sensor such as TiO 2 is selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…Transition-metal doped TiO 2 -based materials have been widely studied for the development of semiconductors with enhanced catalytic activity. The incorporation of transition metals into the lattice of TiO 2 induces the formation of new energy levels near the conduction band. For instance, cobalt-modified TiO 2 anatase presented ferromagnetism with n-type semiconducting properties. , Cobalt might possibly occupy an interstitial position in the TiO 2 lattice because of its relatively larger size compared to that of titanium . Spectroscopic determinations revealed that cobalt-doped TiO 2 exhibits band gap narrowing .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cobalt-modified TiO 2 anatase presented ferromagnetism with n-type semiconducting properties. 12 , 13 Cobalt might possibly occupy an interstitial position in the TiO 2 lattice because of its relatively larger size compared to that of titanium. 14 Spectroscopic determinations revealed that cobalt-doped TiO 2 exhibits band gap narrowing.…”
Section: Introductionmentioning
confidence: 99%